Computer teaching methods effect on students' achievement and attitude - David, Monette C. (2008)
This investigation studied the effect of computer literacy on students' achievement and attitude using 2 Computer teaching methods in 2 Intermediate Computer classes. The respondents were 68 Grade Five students, 35 participated in an experimental approach which used Web based Instruction and Hands-on method, while 33 belong to the control group which used Demonstration with Hands-on method. Two sets of instruments were used--the Personal Data Sheet and Attitude Questionnaire and the Pretest and Posttest about the presentation software. Based on the results, there was no significant difference on achievement and attitude of respondents using the 2 different modes of instruction. It was recommended that teachers continuously research for free educational websites and conduct in-service trainings to teach subject teachers the application of computer technology in their teaching.
Thesis (M.A. Educational Technology)--University of the Philippines, Diliman.
Keywords: Computer literacy -- Philippines -- Manila Metropolitan Area; Teaching -- Philippines -- Manila Metropolitan Area; Educational technology -- Philippines -- Manila Metropolitan Area; Computer-assisted instruction -- Philippines -- Manila Metropolitan Area